Radiotherapeutic implications of the updated ICRP thresholds for tissue reactions related to cataracts and circulatory diseases. (October 2018) - Dauer, L.T.; Yorke, E.; Williamson, M.; Gao, Y.; Dauer, Z.L.; Miller, D.L.; Vañó, E.
Radiation therapy of cancer patients involves a trade-off between a sufficient tumour dose for a high probability of local control and dose to organs at risk that is low enough to lead to a clinically acceptable probability of toxicity. The International Commission on Radiological Protection (ICRP) reviewed epidemiological evidence and provided updated estimates of 'practical' threshold doses for tissue injury, as defined at the level of 1% incidence, in ICRP Publication 118 . Particular attention was paid to cataracts and circulatory diseases. ICRP recommended nominal absorbed dose threshold for these outcomes as low as 0.5 Gy. Threshold doses for tissue reactions can be reached in some patients during radiation therapy. Modern treatment planning systems do not account for such low doses accurately, and doses to therapy patients from associated imaging procedures are not generally accounted for. While local control is paramount, the observations of ICRP Publication 118 suggest that radiation therapy plans and processes should be examined with particular care. The research needs are discussed in this paper.